In-person versus virtual administration of the American College of Rheumatology gold standard cognitive battery in systemic lupus erythematosus: Are they interchangeable?. (May 2023) - Barraclough, ML; Diaz-Martinez, JP; Knight, A; Bingham, K; Su, J; Kakvan, M; Grajales, C Muñoz; Tartaglia, MC; Ruttan, L; Wither, J; Choi, MY; Bonilla, D; et al.
Objective: During the COVID-19 pandemic, many research studies were adapted, including our longitudinal study examining cognitive impairment (CI) in systemic lupus erythematosus (SLE). Cognitive testing was switched from in-person to virtual. This analysis aimed to determine if the administration method (in-person vs. virtual) of the ACR-neuropsychological battery (ACR-NB) affected participant cognitive performance and classification. Methods: Data from our multi-visit, SLE CI study included demographic, clinical, and psychiatric characteristics, and the modified ACR-NB. Three analyses were undertaken for cognitive performance: (1) all visits, (2) non-CI group visits only and (3) intra-individual comparisons. A retrospective preferences questionnaire was given to participants who completed the ACR-NB both in-person and virtually. Results: We analysed 328 SLE participants who had 801 visits (696 in-person and 105 virtual). Demographic, clinical, and psychiatric characteristics were comparable except for ethnicity, anxiety and disease-related damage. Across all three comparisons, six tests were consistently statistically significantly different. CI classification changed in 11/71 (15%) participants. 45% of participants preferred the virtual administration method and 33% preferred in-person. Conclusions: Of the 19 tests in the ACR-NB, we identified one or more problems with eight (42%) tests when moving from in-person to virtual administration. As the use of virtual cognitive testing will likely increase, these issues need to be addressed – potentially by validating a virtual version of the ACR-NB. Until then, caution must be taken when directly comparing virtual to in-person test results. If future studies use a mixed administration approach, this should be accounted for during analysis.